THE IMPACT OF MONETARY EXPANSION ON THE US TELECOMMUNICATIONS SECTOR (Perner's Contacts, 2014)
This study focuses on how the current macroeconomic situation influences the telecommunications sector. The analysis suggests that telecommunications indices and thus telecommunications sectors are less influenced by current monetary expansion than is the US equity market as a whole. Also demonstrated is that the influence of the latest economic crisis on the telecommunications industry has been less cyclical than it has been for the stock market as a whole as measured by the S&P 500 US equity index.